Penetrating Head Injury by a Key: A Case Report - Oley, Maximillian C.; Prasetyo, Eko; Tjungkagi, Ferdinan; Manuhutu, Yovanka N.; Sitorus, Edwin H. (Medical Scope Journal, 2025)
Abstract: Penetrating head injury is defined as head trauma caused by an object that penetrates the skull and the underlying duramater. We reported a 22-year-old man who came to the hospital with a motorcycle key stuck into the back of his head after a fight with his friend approximately one hour before admission. The patient was fully conscious. History of projectile vomiting, and seizures were denied, and there were no other neurological deficits. Blindly removing the key can damage the neural tissue and can cause secondary injury to the brain and surrounding blood vessels. The primary goal of treatment for patients with suspected traumatic brain injury is to prevent secondary brain injury and infection. The removal of the object safely, debridement of the damaged parenchyma, removal of the hematoma, and closure of the injured dura and skin are the main goals of surgical treatment for penetrating head injuries. In this case, motor key evacuation was performed followed by craniotomy and debridement. The prognosis was good, and there was no neurological deficit. In conclusion, complete and adequate care is essential for patients with penetrating brain injuries. The strategy for treating these injuries is primarily surgery with the aim of preventing secondary brain injury and infection. According to existing research, antibiotics should be given for an indefinite period after surgery. Keywords: penetrating head injury; motorcycle key